Mutation study of spanish patients with hereditary hemorrhagic telangiectasia and expression analysis of endoglin and ALK1 (2006)
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant and age-dependent vascular disorder originated by mutations in Endoglin (ENG) or activin receptor-like kinase-1 (ALK1, ACVRL1) genes. The first large series HHT analysis in Spanish population has identified mutations in 17 unrelated families. Ten different mutations in ALK1 and six in ENG genes were found. Six unrelated families had a mutation in ENG gene, four representing new mutations, p.Y258fs, pV323fs, p.F279fs (c.834_837del CTTC), and p.F279fsdupC. Eleven unrelated families harboured mutations in ALK1; ten were new mutations identified as p.H328P, p.R145fs, p.G68C, p.A377T, p.H297R, p.M376T, p.C36Y, p.H328P, p.T82del and p.R47P. Overall, ALK1 mutations (HHT2) were predominant over ENG mutations (HHT1), in agreement with data reported for other Mediterranean countries (France, Italy), but at variance with Northern Europe or North America. Endoglin expression in HHT1 or HHT2 activated monocytes and blood outgrowth endothelial cells (BOECs) from older patients was well below the theoretical 50% level expected from the HHT1 haploinsufficiency model, suggesting that the pathogenic endoglin haploinsufficiency leading to the HHT phenotype is age-dependent. Interestingly, ALK1 protein levels of HHT BOECs in some missense ALK1 mutants were similar to controls. In vitro expression of these ALK1 constructs suggests that, in addition to the haploinsufficiency model, certain ALK1 mutants may inhibit the function of the wild type allele. © 2006 Wiley-Liss, Inc.